Six new species of the genus Meleonoma Meyrick, 1914 (Lepidoptera: Autostichidae) from China - Zhu, Xiaoju; Wang, Shuxia (Zootaxa, 2024)
Six new species belonging to the malacobyrsa species group of the genus Meleonoma Meyrick (Autostichidae, Periacminae) are described from China: M. avicapitata sp. nov., M. bitaeniana sp. nov., M. dorsidentata sp. nov., M. hirsuta sp. nov., M. longibursoides sp. nov. and M. spiculata sp. nov. Images of adults and genitalia are provided.